مسالك الكشف عن حكمة تشريع الأحكام عند الإمام القفال الشاشي: Methods of Identification of the Wisdom in Legislation of Islamic Jurisprudence According to Imam Al-Qaffāl al-Shāshi - Ahmad, Maad; Yosef Niteh, Muhammad; Talib, Hasliza (Jurnal Fiqh, 2022)
Imam Al-Qaffāl al-Shāshi was an eminent scholar of the Shafi’i school of fiqh who emphasised on the field of reasoning (ta’lil) and the identification of the wisdom in Islamic jurisprudence. His work “Maḥāsin al-Sharī’ah” contains myriad exposition on the wisdom of rulings, including those considered irrelevant and conjectural. This article discusses the method of exposition employed by Imam Al-Qaffāl in his book. This article is crucial, as accurate knowledge in the wisdom of legislation has a significant relationship with the acceptance of a ruling. It will enhance the certainty and assurance of a Muslim, leading to more openness in the acceptance and adherence to Islamic sharia. This article aims to expose in detail the methods used by Imam Al-Qaffāl in his work. The researcher used the method of descriptive research and analysis for the study. All data in “ Maḥāsin al-Sharī’ah “ related to reasoning (ta’lil) and wisdom of legislation were collected and analysed thematically. The study found that Imam Al-Qaffāl al-Shāshi built his thoughts in the process of the identification of wisdom based on six methods which include employing evidence from the Holy Quran, hadiths, Ijma’, Fatāwa of Sahābah, logical thinking, and the agreement of Islamic scholars before him.